Malgré tout… l’image manque (Cinéma & Cie. Film and Media Studies Journal, 2015)
Facing the genocide perpetrated by the Khmer Rouge in Cambodia, The Missing Picture (2013) by Rithy Panh is an intimate meditation on the limits and the power of cinema. The same query drives Công Binh, la longue nuit indochinoise (2013), the documentary essay that Lâm Lê dedicated to worker-soldiers recruited by force in French Indochina to serve as slave labor in France during World War II. Both films make extensive use of so called “archive images”: totalitarian propaganda films, photographs, and documents originating from the colonial administration, as well as newsreels, etc. These archives corroborate the fantasy of all powers: that of a mass of faceless bodies. There are only two reverse shots possible for false image of the Khmer Rouge: either the shots made by Rithy Panh – tiny colored clay figurines, representing in miniature the formerly murdered missing bodies; or, in Lâm Lê’s movie, interrupting the sequences of oral testimonies and archive images, the choreographed scenes and a water puppet show which transpose the distress of families who stayed in Vietnam and were left without news for years. What is at stake in the rhapsodic construction of the two films is not the giving of an image where it is missing, but encouraging viewers to encounter a work of imaginary elaboration.